2014
DOI: 10.1089/lap.2014.0194
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic Versus Open Inguinal Hernia Repair in Pediatric Patients: A Systematic Review

Abstract: In this systematic review, it seems that LH is faster than OH for bilateral hernias, whereas there is no significant difference in terms of operative time for unilateral inguinal hernia repair. Recurrence rate is similar for both techniques. As for other complications such as wound infections, it is higher for OH compared with LH, especially in infants. A prospective comparative study is necessary on this topic to strongly support the results of our systematic review.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
91
1
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 130 publications
(98 citation statements)
references
References 55 publications
2
91
1
4
Order By: Relevance
“…Previous reports stated that laparoscopic contralateral internal inguinal ring observation was attempted from the early 1990s [25]. A contralateral PPV was seen in 6-66 % of cases [16,[25][26][27][28][29][30][31][32]; the range is very wide. This seems to be because the way of observing the contralateral internal ring varied in each study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous reports stated that laparoscopic contralateral internal inguinal ring observation was attempted from the early 1990s [25]. A contralateral PPV was seen in 6-66 % of cases [16,[25][26][27][28][29][30][31][32]; the range is very wide. This seems to be because the way of observing the contralateral internal ring varied in each study.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, there is a trend for increased reports of extraperitoneal closure because of its ease of use and good results. There are some comparative reports between laparoscopic hernia repair and open repair, including a systematic review [16][17][18][19][20][21][22]. However, few reports have compared extraperitoneal closure with conventional open hernia repair, especially large case series in one institution [22].…”
mentioning
confidence: 99%
“…17,20 Both studies showed no significant difference in recurrence rate. Esposito et al 17 reported a 1.4% recurrence rate following laparoscopic repair and 1.6% following open repair.…”
Section: Open Versus Laparoscopic Surgerymentioning
confidence: 91%
“…17,20 Both studies showed no significant difference in recurrence rate. Esposito et al 17 reported a 1.4% recurrence rate following laparoscopic repair and 1.6% following open repair. For operating time, they noted a significantly shorter time for laparoscopic repair of bilateral hernia when compared with an open approach.…”
Section: Open Versus Laparoscopic Surgerymentioning
confidence: 91%
See 1 more Smart Citation